Could the directly measured data of transpiration be replaced by model outputs? - Středová, Hana; Klimešová, Jana; Středa, Tomáš; Fukalová, Petra (Contributions to Geophysics and Geodesy, 2020)
Successful upscaling of the direct measurement of evapotranspiration at individual plant level to canopy level with specific microclimatic conditions has recently received considerable attention of scientific community. And since the knowledge of transpiration is among important inputs of various experiments on solitary plant level the paper employs the reverse approach – the downscaling from the canopy to individual plant. The main task of the study is thus to compare Penman–Monteith method of computing potential evapotranspiration with directly measured values of transpiration of maize. Since the model deals with canopy level and the direct measurement is being carried out on level of individual plants, this comparison answers the question if the time-consuming and demanding measurement of transpiration on plant level could be substitute by relative easily reachable model outputs. The results shown that evapotranspiration of maize computed by Penman–Monteith model cannot be successfully downscaled back to the solitary plant level. The correlation coefficient between these two data series for three individual phenological stages vary from 0.5831 to 0.7803 (α = 0.01) while for whole growing period regardless phenological stage is 0.6925 (α = 0.01). The directly measured data of transpiration cannot by simply replaced by modelled data, but their application after conversion using regression equations is possible with certain level of inaccuracy.